Two Modes of the Pion Decay in Weak Interaction - Nhu Xuan, Nguyen; Toan Thang, Vu (VNU Journal of Science: Mathematics - Physics, 2024)
This work presents traditional methods and new results for calculation of decay rates of positive pion in the Standard Model. Both the phenomenological and theoretical knowledge of the decays were presented. The calculation of the decays of the pion into three particles from isotopic spin conservation and the principle of vector current conservation was updated. The comparison was made with exclusive branching ratio data and inclusive charged particle distribution measurements in pion decays; The difficulty in accounting for all the one charged-particle decays as a sum of exclusive decay modes has been discussed.